Surface Modification of Cobalt‐Manganese Mixed Oxide and Its Application for Low‐Temperature Propane Catalytic Combustion. Issue 4 (21st January 2021) - Liu, Yihao; Zhao, Peng; Sun, Liang; Feng, Nengjie; Wang, Lei; Wan, Hui; Guan, Guofeng
Abstract: The Co−Mn mixed metal oxide was firstly fabricated using Co(NO3 )2, KMnO4 and K2 CO3 . The tuned catalysts, donated as xM‐Co3 Mn1 (x=0, 0.025, 0.05 and 0.1), were synthesized by selective dissolve method (SD). The physicochemical properties induced by different acid concentrations on catalysts were explored via a series of characterization techniques. Compared with the original material, the catalysts treated by SD had higher advantages in enriching crystal defects, surface Co 2+ and adsorbed oxygen species as well as increasing the specific surface areas (SSA). Among acid‐treated catalysts, 0.05 M‐Co3 Mn1 exhibited the best catalytic activity, while the T50 and T90 were 71 and 117 °C lower than the original one. Meanwhile, 0.05 M‐Co3 Mn1 showed excellent stability and great regeneration ability. Abstract : In this work, the Co−Mn mixed oxide was prepared via a coprecipitation method following a selective dissolve method. The K element, acting as the template, could be removed after acid etching. Meanwhile, a large number of surface defects would emerge, which was beneficial to the activating of oxygen species and accelerating propane combustion. Among all the catalysts, 0.5 M‐Co3 Mn1 showed a competitive activity with the lowest T90 at 275 °C.